Pengelolaan Kawasan Hutan Lindung Di Unit Pelaksana Teknis Kesatuan Pengelolaan Hutan Mata Allo Kabupaten Enrekang - Hastuti, Hastuti; Mappamiring, Mappamiring; Abdi, Abdi (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This research is aimed to know how the management of protected forest in UPT of forest management unit V Mata Allo Enrekang Regency. Kind of this research with 6 persons as the subject includes the head of forest management unit V Mata Allo Enrekang Regency, the head of planning and utilization of forest section, forest ranger, and the head of protection an empowerment of society section. The data was collected through observation, interview, and documentation, while the data analysis was collected through data reducation, presentation of the data, anfd the conclusion. The research shows that the management unit V Mata Allo, Enrekang Regency can be categorized as good. It is proved by the planning, organizing, implementation, and supervision, but is it not good enough and it still needs to be improved. The supporting factor in managing this protected forest areas is the principle of “sustainable forest, society welfare”, and the nhibitor fastor is the limited of human recssources in managing the forest.